The Students’ Perception of Using Visual Literacy in English Language Learning: A Descriptive Study - Fauzi, Fatih Al; Saputri, Anggun; Sabartono, Ribut (Universitas Nurul Jadid, 2024)
English as a global lingua franca presents challenges for students in understanding the language in Indonesia, where English is taught as a foreign language. This study aims to explore students' perceptions of the use of visual literacy in English language learning. The use of visual literacy, such as images and videos, has been shown to help improve students' comprehension and engagement in the learning process. The research method used is a descriptive qualitative approach involving seventh-grade students at a middle school in Jember, Indonesia. Data were collected through observations and interviews. The results showed that visual literacy has a positive impact on students' understanding of English language material. Students find it easier to grasp concepts when supported by visual media. Additionally, the use of visual literacy also increases students' motivation and interest in learning, making the learning process more interactive and enjoyable. In the independent curriculum, English language learning encompasses six skills: listening, speaking, reading, writing, reflecting, and presenting, all of which can be supported by the use of visual literacy. Visual literacy not only facilitates the understanding of vocabulary but also encourages students to think critically and creatively through visual interpretation. This creates a more dynamic learning environment and fosters active participation from students. The conclusion of this study is that visual literacy can be an effective tool in enhancing the quality of English language learning, particularly in helping students to understand or remember vocabulary and enhancing students’ English language skills.